2007
DOI: 10.1029/2006rs003553
|View full text |Cite
|
Sign up to set email alerts
|

Initial results from SKiYMET meteor radar at Thumba (8.5°N, 77°E): 2. Gravity wave observations in the MLT region

Abstract: [1] In the present communication, allSKy interferometric METeor (SKiYMET) radar observations of gravity wave activity in the mesosphere lower thermosphere (MLT) region over Thumba (8.5°N, 77°E) are presented. The present meteor radar system provides hourly zonal and meridional winds in the MLT region, which can be readily used for studying the tides, planetary waves, gravity waves of periods 2-6 hours, and other long period oscillations in this region. However, these hourly winds are not sufficient for studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Several observational techniques widely employed for the study of gravity waves right from early years have been the Rocket soundings (e.g., Eckermann et al 1994), Aircraft/Balloon measurements (Nastrom and Fritts 1992), Wind profilers, Radars (Tsuda et al 1989;Riggin et al 1997;Kumar 2006Kumar , 2007aKumar et al 2007), Lidars (Wilson et al 1991a, b;Beatty et al 1992;Deepa et al 2006;Antonita et al 2007Antonita et al , 2008a, Radiosondes (Wang and Geller 2003;Tsuda et al 2004), and satellite observations in more recent times (Wu and Waters 1997;Namboothiri et al 2008;Preusse et al 2009). When most of these ground based observational techniques have limitations of spatial coverage, satellite observations enable global study and spatial characterization of gravity waves.…”
Section: Introductionmentioning
confidence: 98%
“…Several observational techniques widely employed for the study of gravity waves right from early years have been the Rocket soundings (e.g., Eckermann et al 1994), Aircraft/Balloon measurements (Nastrom and Fritts 1992), Wind profilers, Radars (Tsuda et al 1989;Riggin et al 1997;Kumar 2006Kumar , 2007aKumar et al 2007), Lidars (Wilson et al 1991a, b;Beatty et al 1992;Deepa et al 2006;Antonita et al 2007Antonita et al , 2008a, Radiosondes (Wang and Geller 2003;Tsuda et al 2004), and satellite observations in more recent times (Wu and Waters 1997;Namboothiri et al 2008;Preusse et al 2009). When most of these ground based observational techniques have limitations of spatial coverage, satellite observations enable global study and spatial characterization of gravity waves.…”
Section: Introductionmentioning
confidence: 98%
“…However, few studies have used meteorwind radar because of the limitations on their spatial and temporal resolution. Those studies that have been made using meteor radar have used either a generalisation of the dual-beam method applied to meteor radial velocities to measure gravity-wave variances and momentum fluxes (e.g., Hocking, 2005;Antonita et al, 2008;Clemesha and Batista, 2007), or restricted themselves to studies of large-scale gravity waves (e.g., Xiong et al, 2003;Manson et al, 2004;Kumar et al, 2007), or subdivided the meteor collecting volume of the radar into adjacent cells (e.g., Yamamoto et al, 1986;Oleynikov et al, 2005). This paper presents a simple new technique for studying highfrequency gravity waves using meteor radar.…”
Section: Introductionmentioning
confidence: 99%
“…Except this peak, the seasonal variations show maximum activity during summer and winter with an additional peak during October. The equatorial and gravity wave activity over low latitudes shows equinoctial maximum in contrast to the quasi 2 day wave activity [ Hirota , 1984; Kumar et al , 2007b]. Earlier observations from midlatitudes reported that the quasi 2 day wave is a summer time phenomenon [ Muller and Nelson , 1978; Manson and Meek , 1986; Merzlyakov et al , 2004; Limpasuvan et al , 2005].…”
Section: Resultsmentioning
confidence: 99%